Application value of plasma Neurofilament light combined with magnetic resonance imaging to comprehensively evaluate multiple sclerosis activity and status - Mi, Feiyue; Wang, Yingchun; Chai, Wenqiang; Chen, Ya; Yin, Xuhua (Frontiers in Neurology, 2023)
Objective Compare the levels of plasma neurofilament light (NfL) in patients with multiple sclerosis (MS) at acute and remission stages and healthy individuals to explore the role of plasma NfL in monitoring the activity and severity of the disease and predicting disease prognosis. Methods Information on healthy individuals and patients with MS who visited the outpatient and inpatient departments of Inner Mongolia Medical University Affiliated Hospital from October 2020 to August 2022 was collected. EDSS assessment and plain scan+enhanced magnetic resonance imaging (MRI). Plasma Nfl levels were measured using Simoa. Moreover, the relationship between the level of Nlf and the disease status of patients with MS was analyzed.. Results Through the self-comparison of the plasma NfL levels of MS patients in the acute and remission stages, it was noted that the levels in the acute stage are higher than those in the remission stage (p < 0.001). Among the plasma NfL levels of healthy individuals and MS patients in the acute and remission stages, there were statistically significant differences (p < 0.001). Furthermore, the plasma NfL level did not correlate with age or course of disease (p = 0.614 and p = 0.058), whereas it correlated with EDSS score, the number of MRI T2 subtentorial and spinal cord lesions, and the number of MRI enhanced lesions (r = 0.789, p < 0.001; r = 0.846, p < 0.001; r = 0431, p = 0.005, respectively). Conclusion Combining the level of plasma NfL with clinical and MRI estimations will be instrumental in monitoring condition changes and optimizing treatments. The level of plasma NfL is related to the activity and severity of MS, and it is expected to become a new biomarker for assessing the activity and disease status of MS.